2017
DOI: 10.1093/cid/cix1111
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon-α–Induced Natural Killer Cell Activation Is Associated With Human Immunodeficiency Virus-1 DNA Decline in Antiretroviral Therapy–Treated HIV-1/Hepatitis C Virus–Coinfected Patients

Abstract: These data suggest that the reduction of viral reservoir cells during treatment with IFN-α is primarily attributable to antiviral activities of NK cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 46 publications
1
27
0
3
Order By: Relevance
“…A clinical trial has already shown that treatment with IFN-␣ prolongs the time to viral rebound following the cessation of ART (60). In another study, NK cell activation was associated with a decline in cell-associated HIV-1 DNA in HIV-1/HCV-coinfected subjects treated with pegylated IFN-␣ and ribavirin (61). While a recent study in SIV-infected monkeys on ART suggested that pegylated IFN-␣2a treatment did not significantly affect the size of the viral reservoir (62), this could potentially be because there was no LRA given in conjunction with this immunomodulatory agent.…”
Section: Fig 6 Ifn-␣ Enhances the Suppressive Capacity Of Vp And Es Cd8mentioning
confidence: 98%
“…A clinical trial has already shown that treatment with IFN-␣ prolongs the time to viral rebound following the cessation of ART (60). In another study, NK cell activation was associated with a decline in cell-associated HIV-1 DNA in HIV-1/HCV-coinfected subjects treated with pegylated IFN-␣ and ribavirin (61). While a recent study in SIV-infected monkeys on ART suggested that pegylated IFN-␣2a treatment did not significantly affect the size of the viral reservoir (62), this could potentially be because there was no LRA given in conjunction with this immunomodulatory agent.…”
Section: Fig 6 Ifn-␣ Enhances the Suppressive Capacity Of Vp And Es Cd8mentioning
confidence: 98%
“…Gibbert et al ( 89 ) demonstrated that IFN-α11-activated NK cells that enabled cytolytic killing of Friend retrovirus-infected cells compared to other subtypes such as IFN-α2 and IFN-α5. Hua et al ( 90 ) recently reported that the treatment of HIV-1/HCV co-infected subjects on HAART with pegylated-IFN-α induced activation of CD56 bright CD16 − and CD56 bright CD16 + NK cells expressing NKG2D an NKp30 that significantly correlated with a decrease in level of HIV-1 viral reservoir in CD4 T cells. Song et al ( 67 ) examined that the effect of IFN-α subtypes on HBV infection and found that IFN-α4 and IFN-α5 correlated with expansion of effector NK cells in both liver and spleen that was associated with better control of HBV replication.…”
Section: Ifn-α Subtypes and Potential For Functional Curementioning
confidence: 99%
“…Interestingly, HIV + individuals with this favorable outcome had higher frequencies of cytotoxic CD56 dim NK cells (Olesen et al 2015), and the authors speculate that this may have resulted from LRA-induced alteration in expression of NK receptor ligands on infected CD4 + T cells. In another study, PEG-IFNα induced NK cell activation in Hepatitis C/HIV-1 coinfected individuals on long-term suppressive cART; there was a significant correlation between CD56 bright NK cell levels and decreases in cell-associated proviral DNA (Hua et al 2017). These results indicate that both types of NK cells may play a role in cytolysis of infected cell targets upon HIV-1 induction.…”
Section: Directing the Immune Response To Effectively Target The Resementioning
confidence: 99%